Three Fundamental Components of the Autopoiesic Leadership Model (Journal of Universal Excellence, 2026)
Research Question (RQ): What type of leadership could be developed upon transformational leadership?Purpose: The purpose of the research was to create a new leadership style. Its variables can be further developed upon transformational leadership variables. Namely, this leadership style is known as a successful leadership style in successful organisations.Method: In the research of published papers from scientific databases, we relied on the triangulation of theories. To clarify the research question, we have researched different authors, who based their research papers on different hypotheses. In some articles, hypotheses were even contradictory.Results: Through the research, we have concluded that authors often changed certain variables when researching the topic of transformational leadership. We have correlated these variables and developed a new model, naming it autopoiesic leadership. Its main variables are (1) goal orientation, (2) emotional sensitivity, and (3) manager’s flexibility in organisations.Organisation: Our research can have a positive effect on managers in terms of recognising the importance of selected variables. Practical application of autopoiesic leadership can imply more efficiency in business processes of a company, increasing its financial performance.Society: Autopoiesic leadership is a leadership style that largely influences the use of the individual’s internal resources. Thus, she or he becomes internally motivated, and this is the basis for quality work. This strengthens employees’ social aspect which consequently also has a positive effect on their life outside the organisational system, i.e. their family and broader living environment.Originality: In the worldwide literature, we have noticed the concept autopoiesis in papers about management subjects, but the autopoiesic leadership model has not been developed so far.Limitations / Future Research: We based our research on the triangulation of theories, which has been limited to three key variables. We could understand this as a limitation of the research. We will continue the research in the future and try to complement or proceed with a further development of the autopoiesic leadership model.
Keywords: transformational leadership; autopoiesic leadership; goal orientation; emotional sensitivity; flexibility